Problem-Based Learning: A Didactic Strategy in the Teaching of System Simulation - Cevallos-Torres, Lorenzo; Botto-Tobar, Miguel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book describes and outlines the theoretical foundations of system simulation in teaching, and as a practical contribution to teaching-and-learning models. It presents various methodologies used in teaching, the goal being to solve real-life problems by creating simulation models and probability distributions that allow correlations to be drawn between a real model and a simulated model. Moreover, the book demonstrates the role of simulation in decision-making processes connected to teaching and learning.
The System Simulation and their Learning Processes -- Process Sampling -- Pseudo-random Numbers and Congruential Methods -- Random Variable Generation Methods -- Monte Carlo Simulation Method -- Case Study: Logistical Behavior in the use of Urban Transport Using the Monte Carlo Simulation Method -- Case Study: Project-Based Learning to Evaluate Probability Distributions in Medical Area -- Case Study: Probabilistic Estimates in the Application of Inventory Models for Perishable Products in SMEs.
Keywords: Computational intelligence; Artificial intelligence; Educational technology; Computer science -- Mathematics; Mathematical statistics; Computational Intelligence; Artificial Intelligence; Digital Education and Educational Technology; Probability and Statistics in Computer Science